Perceptions and experiences of Korean American older adults with companion robots through long-term use: a comparative analysis of robot retention vs. return - Lee, Othelia EunKyoung; Yun, Ji-Chan; Park, Do-Hyung (Frontiers in Public Health, 2024)
To date, limited research has been conducted on technology use among socially marginalized groups, such as older immigrants who may have limited digital literacy. This pilot study aims to explore Korean American older adults’ perceptions and experiences with a companion version of the social robot, Hyodol. We hypothesize that the Hyodol robot’s social presence may facilitate technology use among this sample. To test this hypothesis, we invited 35 Korean American older adults to interact with Hyodol SAR over a four-month period. This extended engagement allowed us to investigate the underlying factors and dimensions shaping users’ perceptions and experiences. We assessed perceptions through measures of robotic attitudes and usability, while user experiences were evaluated using overall assessment questions and behavioral indicators, such as instances where participants showed the robot to others. We conducted a comparative analysis between participants who chose to keep the robot (“Keepers”) and those who opted to return it (“Returners”), providing insights into how each group utilized and interpreted the robots. Additionally, we examined the reasons Returners decided to not to retain the robot, aiming to identify barriers to acceptance and engagement. Our results indicated that participants’ experiences of warmth and competence while interacting with the Hyodol robots did not significantly differ between the Keepers and Returners. However, distinct patterns emerged in their utilization and interpretation of the robot; the 24 Keepers demonstrated a more intimate level of engagement compared to the 11 Returners. In an era characterized by the growing integration of AI in human care, our findings suggest that social presence became valuable concepts for developing robot companions to enhance their effectiveness.